2006
DOI: 10.1088/0022-3727/39/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Spectral control of emissions from tin doped targets for extreme ultraviolet lithography

Abstract: We have investigated the unresolved transition array (UTA) emission around 13.5 nm from solid density tin and tin doped foam targets. Extreme ultraviolet (EUV) spectral measurements were made in the wavelength region 11–17 nm using a transmission grating spectrograph and the EUV in-band conversion efficiency was measured using an absolutely calibrated EUV calorimeter. The aim of this work was to optimize the UTA emission with the proper density of tin dopant in low-Z foam targets. The addition of tin as an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 22 publications
4
36
0
2
Order By: Relevance
“…The selection of this laser irradiance is based on the fact that our EUV spectroscopic studies showed the unresolved transition array ͑UTA͒ around 13.5 nm from tin plasma to peak at this intensity level using a 60 m spot size. 38 The figure indicates that the SMB fit is in relatively good agreement with the experimental observed TOF curve.…”
Section: A Time Of Flight Studiessupporting
confidence: 66%
“…The selection of this laser irradiance is based on the fact that our EUV spectroscopic studies showed the unresolved transition array ͑UTA͒ around 13.5 nm from tin plasma to peak at this intensity level using a 60 m spot size. 38 The figure indicates that the SMB fit is in relatively good agreement with the experimental observed TOF curve.…”
Section: A Time Of Flight Studiessupporting
confidence: 66%
“…For example, the UTA emission around 13.5 nm is mainly contributed by Sn 8+ to Sn 13+ ions. 17 In a laser-produced plasma, the velocity of the ions is dependent on their charge state and highly charged ions move with faster expansion velocity. This can be understood by considering the plume expansion in the initial stages where electrons strive to overtake the ions resulting in a space charge field that accelerates ions causing higher velocity for highly charged ionic states.…”
Section: Resultsmentioning
confidence: 99%
“…Low density Sn-doped plastic foam, 4,5 Sn-doped water droplet targets, 6 and fine Sn particles driven by gas puff have been investigated as masslimited targets to mitigate Sn particles. However, extra C, O, and H ions with very high velocity are inherently generated from these targets.…”
mentioning
confidence: 99%